Circuitos cortos de comercialización agroecológica en el Ecuador (2017)
ABSTRACT: This article analyzes the factors that promote the sustainability of short circuits of marketing of the Unión de Organizaciones Productoras Agroecológicas y de Comercialización Asociativa de Tungurahua (PACAT) in Ecuador. Based on document review, key informant interviews and visits to their farms, the authors found that the viability of this economic strategy depends on the strength of informal institutions that sustain local organization and reduce transaction costs, thereby improving economic efficiency. In this way short circuit marketing can contribute to the proliferation of agro-ecological production. In addition, the study indicates the administrative challenges that informal organizations face when attempting to become formal, legal entities.